Jean Baudrillard and radical education theory : turning right to go left - Kline, Kip; Holland, Kristopher J. (Brill guides to scholarship in education ;, 2021)
"In Jean Baudrillard and Radical Education Theory: Turning Right to Go Left, the authors argue that Baudrillard has been underappreciated in philosophical and theoretical work in education. They introduce him here as an important figure in radical thought who has something to add to theoretical lines of inquiry in education. The book does not offer an introduction to Baudrillard. Rather, his corpus is mined in order to describe how it functions as a counter to the code of education, rational thought, critical reason, etc. In effect, they establish that Baudrillard advocates for a counter-path to thinking that can shake us out of our ready-made thoughts and realize the radical potential for change"--